The role of practical shooting in system of police shooting training: psychological component - V. V. Fedorov; O. B. Piskunova (Law and Safety)
Psychological unpreparedness of police officers to firefight is often the cause of serious consequences, in particular their death. Although much attention has been already paid to the psychological training of law enforcement officers in general and to the use of firearms in the scientific literature, such studies often just outline the problems, but do not suggest the ways to overcome them. The authors of the article aim to analyze the factors influencing the state of psychological readiness of a police officer to use a firearm while performing service duties, and to develop recommendations that should contribute to the formation of a state of psychological readiness, taking into account the specifics of practical shooting. It has been emphasized that firefight requires from a police officer not only skillful handling of weapons, but also a number of thought processes in a situation of partial or complete uncertainty, which affects the psychological readiness to use firearms. The authors have made an analogy between the situations of firefight of police officers while performing service duties and the conditions created for participants in practical shooting competitions. According to the authors, long-term training, regular practice of basic exercises to improve firearms skills, as well as the introduction of variability of scenarios for the deployment of firefight situations using elements of practical shooting can minimize the negative impact on the mental processes of police officers. It has been offered to introduce elements of practical shooting into the system of fire training of police officers and to improve the current Shooting Course, approved by the order of the Ministry of Internal Affairs of Ukraine dated from April 26, 2019, No. 334, which should allow modeling multiple scenarios of police behavior in firefight situations during training shootings and increase the psychological readiness of police officers to use firearms.